Controlled molecular orientation of inkjet printed semiconducting polymer fibers by crystallization templating - Rödlmeier, Tobias; Marszalek, Tomasz; Held, Martin; Beck, Sebastian; Pucci, Annemarie; Zaumseil, Jana (Chemistry of materials, 2017)
Here we present the controlled deposition of highly aligned poly(3-hexylthiophene-2,5-diyl) (P3HT) fibers by inkjet printing. The functional ink consists of the crystallization agent 1,3,5-trichlorobenzene (TCB), the carrier solvent chlorobenzene, and the semiconducting polymer P3HT. The inkjet printing process was designed in such a way that the drying zone migrates in the printing direction, effectively growing the TCB out of solution and forcing the P3HT chains to align in the printing direction. The films are deposited in arbitrary shapes on a variety of substrates, thus demonstrating the full freedom of design necessary for the digital fabrication of future integrated circuits. We demonstrate by optical and structural investigations that P3HT arranges in a nontrivial empty-core-shell structure with the long molecular axis in the fiber direction while the short axis extends in a radial fashion. Such arrangement induces a fourfold increase in field-effect mobility along the fiber direction as compared to the isotropic printed reference.